INFECTION-ASSOCIATED DEMENTIA - Harahap, Herpan Syafii; Rianawati, Sri Budhi (Malang Neurology Journal, 2015)
Central nervous system infection may decrease cognitive function in broad spectrum, ranged from mild cognitive impairment to infection-associated dementia. Infection-associated dementia is a dementia which develops concomitantly or lately after central nervous system infection by any microorganism. Some study showed infection-associated dementia was likely developing as the secondary neuronal response to the activation of immune cell in the brain activated by infectious agent. Screening and formal neuropsyichological testing are the most important examination modalities for the diagnosis of infection associated dementia. The availability of functional radiological examination techniques are useful for identifying of brain function and visualizing the brain activities in vivo. The recent modality treatments for infection-associated dementia are insignificantly different with the modality treatments for other dementia. These treatment are consists of pharmacological and non-pharmacological treatments.